Thermoelectricity in Quantum Hall Corbino Structures - Real, Mariano (2020)
We measure the thermoelectric response of Corbino structures in the quantum Hall effect regime and compare it with a theoretical analysis. The measured thermoelectric voltages are qualitatively and quantitatively simulated based upon the independent measurement of the conductivity, indicating that they originate predominantly from the electron diffusion. In contrast to earlier Hall-bar experiments, electron-phonon interaction does not lead to a phonon-drag contribution. This implies a description of the Onsager coefficients on the basis of a single transmission function, from which both thermovoltage and conductivity can be predicted with a single fitting parameter. Furthermore, it lets us predict a figure of merit for the efficiency of thermoelectric cooling, which becomes very large for partially filled Landau levels and high magnetic fields.